Direct observation of half-metallicity in the Heusler compound Co 2 MnSi - Jourdan, Martin; Minar, Jan; Braun, J.; Kronenberg, A.; Chadov, Stanislav; Balke, Benjamin; Gloskovskii, A.; Kolbe, M.; Elmers, H. J.; Schoenhense, Gerd; Ebert, H.; Felser, Claudia; et al. (Nature Communications, 2014)
Ferromagnetic thin films of Heusler compounds are highly relevant for spintronic applications owing to their predicted half-metallicity, that is, 100% spin polarization at the Fermi energy. However, experimental evidence for this property is scarce. Here we investigate epitaxial thin films of the compound Co2 MnSi in situ by ultraviolet-photoemission spectroscopy, taking advantage of a novel multi-channel spin filter. By this surface sensitive method, an exceptionally large spin polarization of (93+7 -11) % at room temperature is observed directly. As a more bulk sensitive method, additional ex situ spin-integrated high energy X-ray photoemission spectroscopy experiments are performed. All experimental results are compared with advanced band structure and photoemission calculations which include surface effects. Excellent agreement is obtained with calculations, which show a highly spin polarized bulk-like surface resonance ingrained in a half metallic bulk band structure. © 2014 Macmillan Publishers Limited. All rights reserved.
CRIS-Team Scopus Importer:2023-03-20